Automatic and manual devices for cardiopulmonary resuscitation: A review. (January 2018) - Remino, Carlo; Baronio, Manuela; Pellegrini, Nicola; Aggogeri, Francesco; Adamini, Riccardo
Rate of survival without any neurological consequence after cardiac arrest is driven not only by early recognition but also by high-quality cardiopulmonary resuscitation. Because the effectiveness of the manual cardiopulmonary resuscitation is usually impaired by rescuers' fatigue, devices have been devised to improve it by appliances or ergonomic solutions. However, some devices are thought to replace the manual resuscitation altogether, either mimicking its action or generating hemodynamic effects with working principles which are entirely different. This article reviews such devices, both manual and automatic. They are mainly classified by actuation method, applied force, working space, and positioning time. Most of the trials and meta-analyses have not demonstrated that chest compressions given with automatic devices are more effective than those given manually. However, advances in clinical research and technology, with an improved understanding of the organizational implications of their use, are constantly improving the effectiveness of such devices.